Final Results of the Randomized Phase II NorCap-CA223 Trial Comparing First-Line All-Oral Versus Taxane-Based Chemotherapy for HER2-Negative Metastatic Breast Cancer - Cinieri, S.; Chan, Arlene; Altundag, K.; Vandebroek, A.; Tubiana-Mathieu, N.; Barnadas, A.; Dodyk, P.; Lazzarelli, S.; Botha, M.; Rauch, D.; Villanova, G.; Coskun, U. (2017)
© 2016 Elsevier Inc.Background: The purpose of this study was to evaluate the efficacy of 3 first-line chemotherapy combination regimens for HER2-negative metastatic breast cancer (mBC). Patients and Methods: In this open-label, 3-arm, randomized phase II trial, patients were randomized to all-oral NORCAP (vinorelbine/capecitabine), GEMPAC (gemcitabine/paclitaxel), or GEMDOC (gemcitabine/docetaxel) as first-line chemotherapy for HER2-negative mBC. Stratification factors were center, previous (neo)adjuvant anthracycline, and age. The primary end point was disease control rate (DCR; complete or partial response, or stable disease for =3 months). Results: The DCR was 73% (95% confidence interval [CI], 59-85) with NORCAP (36 of 49 patients), 78% (95% CI, 64-88) with GEMPAC (39 of 50 patients), and 80% (95% CI, 66-90) with GEMDOC (40 of 50 patients). Objective response rates were 33% (16 of 49 patients), 24% (12 of 50 patients), and 50% (25 of 50 patients), respectively; median progression-free survival was 7.6, 9.0, and 11.4 months, respectively. Median overall survival was 30 to 31 months with all regimens. The most common Grade =3 adverse event with each regimen was neutropenia (24 patients [50%], 23 patients [46%], and 43 patients [86%], respectively). The most common nonhematological Grade =3 adverse event was fatigue. Grade 2 alopecia occurred in 36 patients (72%) who received GEMPAC and 38 patients (76%) who received GEMDOC, but only 4 patients (8%) who received NORCAP. There was no evidence of a detrimental effect of NORCAP on quality of life. Conclusion: All-oral NORCAP is an active first-line chemotherapy regimen and might be offered as an alternative to first-line taxane-based therapy for HER2-negative mBC, particularly if patients wish to avoid alopecia or frequent intravenous administrations.